Assessing dengue outbreak areas using vector surveillance in north east district, Penang Island, Malaysia - Ahmad, Mohiddin; Zairi, Jaal; Asmalia, Md Lasim; Hamady, Dieng; Wan Fatma, Zuharah (Elsevier (Singapore) Pte Ltd, 2015)
Objective